Pengadaan Sarana Saluran Air Bersih Antara CV. Bangun Cemerlang dengan PDAM Kota Negara Menurut Perpres Nomor 16 Tahun 2018 - I Putu Bagus Ariana; I Nyoman Putu Budiartha; I Wayan Arthanaya (Warmadewa Press, 2021)
Water is one of the vital resources for human life and nature. On a wider scale, clean water is essential for social and economic development. This research aims to determine the form of cooperation between PDAM and Cv. Bangun Cemerlang whether it is in accordance with PERPRES Number 16 of 2018. This research method is normative law using a conceptual approach and a statutory approach. Before being used for living purposes, water must first be processed to benefit public health. In this case, the role of the Government is required in regulating and managing the fulfillment of clean water needs for the community through an important production branch of the government, namely the Regional Drinking Water Company (PDAM). The results of this study indicate that the collaboration between the government and Cv. Bangun Cemerlang has taken place in accordance with applicable regulations and in accordance with PERPRES Number 16 of 2018. In accordance with applicable laws and regulations in Indonesia, the government is responsible for the quality of water that reaches the public and the public can make complaints to the government as a form of service protest. given with the aim that in the future it can provide better service